Conceptualizing health literacy promotion in second language courses based on a realistic review. (30th September 2020) - Harsch, S; Bittlingmayer, U
Abstract: Background: Second language courses (SLC) and adult basic education courses are considered appropriate settings for promoting health literacy (HL) of vulnerable and hard-to-reach migrants and refugees. Yet, these courses and the process of HL promotion in SCL are not yet empirically well-understood. In the project SCURA, funded by the German Federal Ministry of Education and Research, we explored the role of SLC in HL promotion and developed interventions to improve the HL of newcomers. This study's aim was to analyze projects on HL promotion in SCL and to develop an empirically based theory of change. Methods: We conducted a systematic literature search on HL and SCL on four databases (PubMed, PsycInfo, ERIC, google scholar) and a free online research. Two researchers screened titles, abstracts and full-text and identified 20 articles of 13 interventions eligible for a realistic review (Pawson 2005). We extracted the context and characteristics of the programs, methods, results, influences and triangulated the data to create a model. Results: Despite the heterogeneous contexts, HL can be successfully promoted in SLC. The theory of change unfolds key program activities, outputs and outcomes, supporting factors and their relationships, and specifies the roles of teachers, health professionals, schools and students. The study reveals factors ensuring sustainability e.g. integrating health topics in the standard SLC, capacity building of teachers and institution, partnerships with local health services and focusing on language for health. Conclusions: HL can be improved in SLC, but interventions need to adapt flexibly to the context and situation. Further relevant factors and process are depicted in the empirical-informed model facilitating the development of interventions and to advance the discussion on HL in SLC. Key messages: Empirical data proves second language courses are adequate settings for promoting health literacy. The empirically-informed theory of change helps to guide the development of promising interventions to develop health literacy in second language courses.